On the nature of hexagonality within the solidification structure of single crystal alloys: Mechanisms and applications. (November 2020) - Strickland, Joel; Nenchev, Bogdan; Perry, Samuel; Tassenberg, Karl; Gill, Simon; Panwisawas, Chinnapat; Dong, Hongbiao; D'Souza, Neil; Irwin, Steve
Abstract: Primary spacing is a key phenomenon during solidification of single crystal alloys. It determines microsegregation, defect formation, the time required to solutionise the solidified structure, and the final performance of single crystal components. A novel stereological characterisation algorithm: Shape-Limited Primary Spacing (SLPS) is developed and applied to study the formation of cellular and dendritic packing patterns in single crystal alloys solidified under different casting conditions. The results reveal the tendency for single crystals to form hexagonally packed structures under steady state conditions, while all other packing arrangements constitute a metastable state. Using the SLPS algorithm, it has been demonstrated that packing pattern formation and local primary spacing can be related to tip growth kinetics. Further, the role of curved isotherms that occur in directional solidification has been identified. Isotherm curvature results in non-uniform liquid compositional gradients developing parallel to a growing solid interface, leading to the formation of metastable packing, low-angle grain boundaries, and porosity formation within the microstructure. Graphical abstract: Image, graphical abstract